Middle ear mucosal regeneration with three‐dimensionally tissue‐engineered autologous middle ear cell sheets in rabbit model. (28th July 2013) - Yaguchi, Yuichiro; Murakami, Daisuke; Yamato, Masayuki; Hama, Takanori; Yamamoto, Kazuhisa; Kojima, Hiromi; Moriyama, Hiroshi; Okano, Teruo
Abstract: The likelihood of recurrent retraction and adhesion of newly formed tympanic membrane is high when middle ear mucosa is extensively lost during cholesteatoma and adhesive otitis media surgery. If rapid postoperative regeneration of the mucosa on the exposed bone surface can be achieved, prevention of recurrent eardrum adhesion and cholesteatoma formation, for which there has been no definitive treatment, can be expected. Suture‐less transplantation of tissue‐engineered mucosal cell sheets was examined immediately after the operation of otitis media surgery in order to quickly regenerate middle ear mucosa lost during surgery in a rabbit model. Transplantable middle ear mucosal cell sheets with a three‐dimensional tissue architecture very similar to native middle ear mucosa were fabricated from middle ear mucosal tissue fragments obtained in an autologous manner from middle ear bulla on temperature‐responsive culture surfaces. Immediately after the mucosa was resected from middle ear bone bulla inner cavity, mucosal cell sheets were grafted at the resected site. Both bone hyperplasia and granulation tissue formation were inhibited and early mucosal regeneration was observed in the cell sheet‐grafted group, compared with the control group in which only mucosal removal was carried out and the bone surface exposed. This result indicates that tissue engineered mucosal cell sheets would be useful to minimize complications after the surgical operation on otitis media and future clinical application is expected. Copyright © 2013 John Wiley & Sons, Ltd.